Exploring the Potential of Strengthtening for Batik Industry in Digital Era (Study of Handmade Batik Kulon Progo of Jogjakarta) - Agustin Windianingsih; Wawang Darmawan; Akhmad Najih (PT FORMOSA CENDEKIA GLOBAL, 2023)
Indonesian Batik is a world cultural heritage that has been admired by UNESCO. The market potential for international batik products has long been a target for batik SMEs, including the production of batik tulis of Sembung Batik from Kulon Progo Regency, Jogjakarta. This study analyzes the constraints on the marketing of batik tulis Sembung Batik and recommends strategies for developing a creative economy by maintaining local wisdom. This study used a descriptive qualitative method and the data collected from Sembung Batik. The findings in this study are that foreign buyers almost never complain the quality of Sembung Batik products, meaning that the quality of the products is able to match the willing of foreign consumers. To keep pace with foreign demand, Sembung Batik needs to expand their marketing network by utilizing digital marketing technology, collaboration between batik SMEs, establishing partnerships with financial institutions and improving foreign language skill to communicate their newest products